Perilaku Memilih Transmigran Jawa = Voting Behaviors of Javanese Transmigrants - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT This research is to see factors which affect community of Javanese transmigrants to define choice in general election. The factors seen from cultural, social, economic, and correlation impact from public policy (laws) elite effects, educational level and age, etc. The subjects of the research are the Javanese transmigrant communities of 4 (four) villages in north of Luwu district. The information derived from key informants of competent respondents of various age elements, educational level, pioneer, job iri community. The data are collected by depth interviews and documents collection which are related and appropriate to the focus of the research, to support analysis by descriptive-qualitative method. The result of this research shows that, voting behaviors of Javanese transmigrants were affected by transmigration impact, Indonesian political change, especially the local government system, party system, election system, and development policy. It correlated to other factors, such as, Javanese cultures, local cultures, social condition, economic, which had many effects on real life of society, especially farmers. Voting behaviors of Javanese transmigrant community were autonomous in nature or rational per individual, but in general, elite mobilization which was affected by traditional domination and current phenomena, with last comparison, so thatvoting choice was an intransitive or temporary. Where one, which constructed orientation to their choice, was aggregation of interest, although its orientation was expectation. Voting behaviors were defined by local interest aggregation. Base used was to establish choice for the DPR RI, DPRD provincial, in the DPRD district. Voting behaviors of transmigrants for DPD (local representative board) . tended to be more autonomous, whereas for president election the first round was mobilization, because competition and evaluation used were still affected by elite aspects having playing a role in certain party. And for second round president election, the society was relatively independent in making decision of their choice, it was constructed by the political system condition, where Megawati experienced de-legimating on her policy in the presidential leadership era.